2019
DOI: 10.1016/j.jclepro.2018.12.322
|View full text |Cite
|
Sign up to set email alerts
|

Environmental, social and economic growth indicators spur logistics performance: From the perspective of South Asian Association for Regional Cooperation countries

Abstract: This article examines the association between green logistics operations, social, environmental and economic indicators of SAARC (South Asian Association for Regional Cooperation) countries. The research used GMM (Generalized Method of Moments) and FGLS (Feasible Generalized Least Squares) two methods to tackle the problems of heterogeneity, serial correlation and heteroskedasticity. The findings show that fossil fuel consumption is at the heart of logistics operations; the more fossil fuel and non-green energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 205 publications
(121 citation statements)
references
References 82 publications
5
109
0
7
Order By: Relevance
“…The ecological modernization theory has become one of the leading perspectives of decarbonization and the role of green practices in business operations (Khan et al, ; Spaargaren, ). The theory argues that modern green technology and innovations (green practices in businesses) enhance environmental performance in terms of reducing the harmful effect on environmental sustainability (Jänicke, ; Spaargaren, ; Zhu, Sarkis, & Lai, ).…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The ecological modernization theory has become one of the leading perspectives of decarbonization and the role of green practices in business operations (Khan et al, ; Spaargaren, ). The theory argues that modern green technology and innovations (green practices in businesses) enhance environmental performance in terms of reducing the harmful effect on environmental sustainability (Jänicke, ; Spaargaren, ; Zhu, Sarkis, & Lai, ).…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Stakeholder theory suggests that firms produce externalities, which can cause stakeholders to put pressure on firms to reduce negative effects, and thus influence on organizational practices (Freeman, ; Lange & Bundy, ). Burrell, Hewlett, Luce, and Frohman () highlighted that most businesses and logistics operations have harmful effects on our society, resulting in environmental degradation and human diseases including ischaemic heart disease, lung cancer, stroke, cholera, amoebiasis, giardiasis, and hepatitis (Acquaye, Yamoah, & Feng, ; Khan et al, ; Khan et al, ). For a couple of decades, companies have been mainly emphasizing on corporate social responsibility so as to significantly mitigate their logistics and manufacturing operations' negative effects on society (Rodríguez, Montiel, & Ozuna, ).…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…A questionnaire survey conducted by Makan and Heyns [55] found that the pressures from consumer, brand protection, top management, and cost-saving and revenue are the major drivers for freight organizations to implement the sustainable initiatives. Khan et al [56] modeled the impact of G&SL performance on the countries' economic development and macro-level social and environmental indicators. Papoutsis et al [57] and Solomon et al [58] both maintained that logistics sustainability is closely related to operational efficiency and social acceptance from an economic and environmental perspective.…”
Section: Evaluation On the Social Environmental And Economic Impactsmentioning
confidence: 99%
“…Sustainability is foremost regarded as a global concept, which implies a certain degree of complexity when applied at the organizational level [24]. More specifically, sustainability issues related to social or environmental performance transcend the boundaries of the organization [26]. Unlike financial reporting boundaries, which rely on the principle of financial control, boundaries concerning sustainability performance explicitly need to consider impacts beyond full organizational control [15].…”
Section: Tbl Principle and Boundary Settingmentioning
confidence: 99%
“…In total, 105 responses were received, of which 31 needed to be deleted because of respondents that dropped out at the beginning of the survey. The division is as follows: clients (12), personnel (26), and broader society (36).…”
Section: Sample Statisticsmentioning
confidence: 99%